Study of submerged breakwaters for erosion mitigation along a Philippine beach coast - Abad, John Paul E.; Cruz, Eric C.; Villalba, Imee Bren O. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Beaches, which are primary natural defences against wave action, are at risk of accelerated erosion due to many factors. Sea level rise, on one hand, contributes to adverse impact of storms on beaches. In addition, human activities aggravate sand volume reduction on beach coasts. This paper aims to study the effectiveness of submerged breakwaters, an offshore coastal defence structure, in mitigating beach erosion. For the first part of the study, ten submerged breakwater projects were documented, and beach responses were visually observed by means of Google Earth application. For the second part, a wave field analysis was conducted in Iba, Zambales using the REF/DIF 1 model. The simulations considered the potentially critical prevailing wind directions at mean sea level (MSL), where wave fields with and without a theoretical submerged breakwater were compared. Results have shown that the structure was effective in dissipating high wave heights proportional to high wave energies. Since high wave energies are associated with high erosional capabilities, it was concluded that submerged breakwaters are effective in mitigating beach erosion as also shown in the documented projects with positive beach responses. With this, coastal practitioners can consider such structures for purposes of beach stabilization and widening.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Beach erosion -- Philippines; Shore protection; Breakwaters